Culture, Gender, Multiculturalism and Coloniality of Power in School Text Books Communication - Ortiz Fernández, Carolina (2010)
What are the images that are transmitted over Peru and eth-nosocial world in terms of gender and power i n t he t ext books of s econdar y s chool communi cat i on? What i s the pl ace of these texts i n the process of consti tuti ng the «nati on state»? Does i t appreciate processes of democratization and intercultural training for citizenship? To answer these questions, as part of multidisciplinary research project on «Communication textbooks and the subject of an inter-cultural images and discourses (secondary level)», this time in the first place I begin with a brief historical reflection on the constitution of «nation states», then explore the images and texts of speeches by high school communication produced by the Editorial Santillana, in particular the texts of fourth and fifth years, and conclude with some final thoughts.